A Lithium Niobate (LiNbO3) - Chalcogenide-Based Thin Film Composite Asymmetric Y-Type On-Chip Wavelength Division Multiplexer - Bowen Liu; Nuo Xu; Wanqi Guo; Xinyue Liu; Baoan Song (IEEE Photonics Journal)
This study presents an on-chip dual-mode multiplexer based on a lithium niobate-sulfide thin-film composite adiabatic coupler. The device integrates two input waveguides with distinct structures into a shared output waveguide, enabling selective mode conversion and combination through precise manipulation of the refractive index distribution. Simulation results demonstrate that the device functions across a broad wavelength range of 1500–1600 nm, achieving a wideband operation with crosstalk below 17 dB and insertion loss under 1.36 dB. Tolerance analysis reveals that the device maintains satisfactory performance even with variations in etching depth and waveguide gap within a ±50 nm range. Experimental results show that the overall coupling efficiency of the device is approximately −27 dB.